Structural and Optical Properties of New Naphthalene and Perylene Imide Imidazoles - Aksakal, Nuray Esra; Bayar, Meltem; Dunnrul, Hakan; Atilla, Devrim; Chumakov, Yurii; Yüksel, Fatma (Taylor & Francis Ltd, 2019)
New unsymmetrically substituted naphthalene and perylene imide imidazoles, N-(2-ethylhexyl)-naphthalene-3,4-(4,5-dicyano-1,2-benzimidazole)-9,10-dicarboxyimide and N-(1-heptyloctyl)-perilene-3,4-(4,5-dicyano-1,2-benzimid-azole)-9,10-dicarboxyimide, were synthesized via condensation reactions of diaminophthalonitrile and aromatic monoimide monoanhydride derivatives. Their structural analyses have been conducted by using general spectroscopic methods including FT-IR, H-1- and C-13-NMR, mass and elemental analysis. The molecular structure of naphthalene derivative was also determined by single crystal x-ray diffraction. Electronic absorption and emission properties were investigated on comparison. For studied compounds, both DFT and TDDFT calculations were carried out with the 6-311G(d,p) basis set, taking into account solvation effects by means of polarizable continuum model as implemented in the Gaussian 09 package.
Keywords: Benzimidazole; fluorescence; naphthalene; perylene; photochemistry